2005
DOI: 10.1634/theoncologist.10-9-728
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel/Carboplatin/Etoposide Versus Paclitaxel/Topotecan for Extensive-Stage Small Cell Lung Cancer: A Minnie Pearl Cancer Research Network Randomized, Prospective Phase II Trial

Abstract: Results. The paclitaxel-carboplatin-etoposide combination produced a significantly higher overall response rate (78% versus 48%), longer median time to progression (7.6 months versus 5.5 months), and greater number of patients free from progression at 1 year (14% versus 8%) compared with paclitaxel plus topotecan. There was no difference in overall survival. Toxicities were similar in the two treatment arms.Conclusions. The paclitaxel-carboplatin-etoposide combination produced a superior overall response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Attempts to improve survival in patients with SCLC have included addition of a third agent such a irinotecan [4] Ifosfamide [5], topotecan [6] and paclitaxel [6] to etoposide and platinum combinations. Other attempts to improve outcomes include increasing dose intensity by either increasing the dose or shortening the interval between cycles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to improve survival in patients with SCLC have included addition of a third agent such a irinotecan [4] Ifosfamide [5], topotecan [6] and paclitaxel [6] to etoposide and platinum combinations. Other attempts to improve outcomes include increasing dose intensity by either increasing the dose or shortening the interval between cycles [7].…”
Section: Introductionmentioning
confidence: 99%
“…The QoL results of our study back the observed survival advantage as well as the decrease of grade 3/4 non-haematological toxicities. The favourable clinical benefit from TEC in patients with extensive disease, previously reported for this regimen by another SCLC study group [34] and regarded as a reasonable palliative standard for patients with ED by a third one [35], might be explained as a result of an optimised regimen for efficient palliation. Higher doses in the CEV arm, if administered as initially planned, would have lead to even more haematological toxicity and worse QoL outcomes in the control arm.…”
Section: Discussionmentioning
confidence: 69%
“…Myelotoxicity, particularly neutropenia, was the main adverse reaction, but only in a small group of patients 60 . However, as with all treatments, there have been some negative trials, for example a paclitaxel–carboplatin–etoposide combination produced a superior overall response rate and time to progression interval in patients with extensive‐stage SCLC compared with paclitaxel and topotecan 61 …”
Section: Chemotherapymentioning
confidence: 99%